ANALISIS GAYA BAHASA DALAM TIGA KUMPULAN CERITA PENDEK KARYA KAKANDA REDI - Fatmawati, Fatmawati; Priyadi, Antonius Totok; Syam, Christanto (Universitas Tanjungpura, 2025)
This research aims to analyze the use of language styles in three short story collections by Kakanda Redi. The method used is a qualitative descriptive method. The data sources for this research are three short story collections by Kakanda Redi. The data is in the form of phrases and sentences that contain language styles. Data collection techniques, namely documentary study, listening and note-taking techniques. The results of the analysis found (1) a group of comparative language styles including similes, metaphors, personification, depersonification, antithesis, pleonasm, periphrasis and correction, (2) a group of conflicting language styles including hyperbole, irony, anticlimax, cynicism and sarcasm, (3) a group of contrasting styles linking language includes metonymy, synecdoche, anthomonation, erotesis, ellipsis, gradation, incidenton and polysidenton, (4) groups of repetition language styles include alliteration, chiasmus, epizeukis, anaphora, epistrophe and mesodiplosis. The results of this research can be implemented for writing teaching materials for Indonesian language learning